2017
DOI: 10.4049/jimmunol.1600810
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Oxidative Phosphorylation In Vivo Restrains Th17 Effector Responses and Ameliorates Murine Colitis

Abstract: Integration of signaling and metabolic pathways enables and sustains lymphocyte function. While metabolic changes occurring during T cell activation are well-characterized, the metabolic demands of differentiated T lymphocytes are largely unexplored. Here we defined the bioenergetics of TH17 effector cells generated in vivo. These cells depend on OXPHOS2 for energy and cytokine production. Mechanistically, the essential role of OXPHOS in TH17 cells results from their limited capacity to increase glycolysis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 70 publications
5
56
0
Order By: Relevance
“…The observed metabolic changes (i.e., up-regulated glycolytic and down-regulated TCA cycle activity leading to consequent reduction in inflammatory cytokine production and anergy) are best explained by the observed H3K27-mediated silencing of key transcription factors, such as MYC, PPARγ, and PPRC1, as a consequence of GSK-J4 treatment (63). Recently, it has been shown that inhibition of mTORC1 signaling rescues ATF4deficient cells from MYC-induced endoplasmic reticulum stress (64).…”
Section: Discussionmentioning
confidence: 99%
“…The observed metabolic changes (i.e., up-regulated glycolytic and down-regulated TCA cycle activity leading to consequent reduction in inflammatory cytokine production and anergy) are best explained by the observed H3K27-mediated silencing of key transcription factors, such as MYC, PPARγ, and PPRC1, as a consequence of GSK-J4 treatment (63). Recently, it has been shown that inhibition of mTORC1 signaling rescues ATF4deficient cells from MYC-induced endoplasmic reticulum stress (64).…”
Section: Discussionmentioning
confidence: 99%
“…The observed metabolic changes-i.e. upregulated glycolytic and downregulated TCA cycle activity leading to consequent reduction in inflammatory cytokine production and anergy- are best explained by the observed H3K27 mediated silencing of key transcription factors such as MYC, PPARg and PPRC1 as a consequence of GSK-J4 treatment (61). Recently, it has been shown that inhibition of mTORC1 signalling rescues ATF4-deficient cells from MYC-induced endoplasmic reticulum stress (60).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we reasoned that this fundamental process is critical for the biology of Th17 cells. Previous studies report that fully differentiated Th17 cells showed increased mitochondrial respiration in comparison to naive CD4 T cells (Franchi et al, 2017;Gerriets et al, 2015). However, it is unknown whether mitochondrial OXPHOS is induced during the process of Th17 lineage commitment.…”
Section: Th17 Cells Actively Utilize Mitochondrial Oxphos To Fuel Optmentioning
confidence: 97%